Sacred Space: Shrine, City, Land
VIII, 344 p.
Keywords: Sacred Space: Shrine, City, Land - a collection of articles that deal with Holy Places from Antiquity to the present; from the lands of the Fertile Crescent to Europe, India, Japan and Mexico; from mountains and seas to temples, cities and countries; from the construction, perception and functioning of sacred sites to the psychotic breakdowns they bring on some visitors.